Determinants and predictive model of failure of surgical repair of obstetric vesico-vaginal fistula in the Democratic Republic of the Congo - Justin Lussy Paluku; Barthelemy Kasi Aksanti; William C. Clemmer; Cathy Mufungizi Furaha; Eugénie Mukekulu Kamabu; Jonathan M. L. Kasereka; Benjamin Kambale Kalole; Olivier Mukuku; Zacharie Kibendelwa Tsongo; Stanis Okitotsho Wembonyama; Charles Wembonyama Mpoy; Jeannot Sihalikyolo Juakali (BMC, 2024)
Abstract Introduction Surgical repair of obstetric fistula aims to restore the anatomical and functional integrity of the urinary tract, enabling affected women to regain their dignity and quality of life. However, such repairs can end in a failure. The aim of this study is to develop a predictive score to identify factors influencing failure of surgical repair of obstetric vesico-vaginal fistula (FSROVVF) in the Democratic Republic of the Congo. Methods This was an analytical cross-sectional study of 318 women with obstetric vesico-vaginal fistula (OVVF) who had undergone surgical management. A bivariate and then a multivariate analysis were performed. Score discrimination was assessed using the ROC curve and C-index, and score calibration using the Hosmer-Lemeshow test. Results Surgical repair of OVVF was unsuccessful in 16.98% of cases (54/318). After logistic modeling, six criteria emerged as predictive factors for FSROVVF: the presence of fibrosis (AOR = 5.01; 95% CI:1.73-14.49), the presence of 2 or more fistulas (AOR = 9.04; 95% CI:3.01-27.13), the association of OVVF with another anatomoclinical entity of fistula (AOR = 3.16; 95% CI:1.09-9.13), the fistula size > 3 cm (AOR = 3.65; 95% CI:1.36-9.76), the peri-operative hemorrhage (AOR = 7.01; 95% CI:2.33-21.03), and the post-operative infection (AOR = 178.89; 95% CI:26.09-1226.64). A score ranging from 0 to 13 points was obtained, of which a value ≤ 5 points defines a low risk of FSROVVF, a value between 6 and 8 points defines a moderate risk and value ≥ 9 points corresponds to a high risk of FSROVVF. The area under the ROC curve of the score is 0.925 with a sensitivity of 61.11%, a specificity of 96.59%, a positive predictive value of 78.57% and a negative predictive value of 92.39%. Conclusion This study demonstrated that the number of fistulas ≥ 2, fistula size > 3 cm, fibrosis, association of OVVF with other types of fistulas, peri-operative hemorrhage, and post-operative infection are factors predictive of FSROVVF. These six factors are key contributors to the score used to predict FSROVVF. Once validated, this score will inform and enable preoperative counseling regarding the prognosis and the chances of a successful outcome of surgical repair of OVVF.